Cryptic Metabolites from Marine-Derived Microorganisms Using OSMAC and Epigenetic Approaches - Cristina Pinedo-Rivilla; Josefina Aleu; Rosa Durán-Patrón (Marine Drugs, 2022)
Marine microorganisms have proven to be a source of new natural products with a wide spectrum of biological activities relevant in different industrial sectors. The ever-increasing number of sequenced microbial genomes has highlighted a discrepancy between the number of gene clusters potentially encoding the production of natural products and the actual number of chemically characterized metabolites for a given microorganism. Homologous and heterologous expression of these biosynthetic genes, which are often silent under experimental laboratory culture conditions, may lead to the discovery of new cryptic natural products of medical and biotechnological interest. Several new genetic and cultivation-based strategies have been developed to meet this challenge. The OSMAC approach (one strain—many compounds), based on modification of growth conditions, has proven to be a powerful strategy for the discovery of new cryptic natural products. As a direct extension of this approach, the addition of chemical elicitors or epigenetic modifiers have also been used to activate silent genes. This review looks at the structures and biological activities of new cryptic metabolites from marine-derived microorganisms obtained using the OSMAC approach, the addition of chemical elicitors, and enzymatic inhibitors and epigenetic modifiers. It covers works published up to June 2021.